Porcine Stomach Smooth Muscle Force Depends on History-Effects - Tomalka, André; Borsdorf, Mischa; Böl, Markus; Siebert, Tobias (Frontiers in Physiology, 2017)
The stomach serves as food reservoir, mixing organ and absorption area for certain substances, while continually varying its position and size. Large dimensional changes during ingestion and gastric emptying of the stomach are associated with large changes in smooth muscle length. These length changes might induce history-effects, namely force depression (FD) following active muscle shortening and force enhancement (FE) following active muscle stretch. Both effects have impact on the force generating capacity of the stomach, and thus functional relevance. However, less is known about history-effects and active smooth muscle properties of stomach smooth muscle. Thus, the aim of this study was to investigate biomechanical muscle properties as force-length and force-velocity relations (FVR) of porcine stomach smooth muscle strips, extended by the analysis of history-effects on smooth muscle force. Therefore, in total n = 54 tissue strips were dissected in longitudinal direction from the ventral fundus of porcine stomachs. Different isometric, isotonic, and isokinetic contraction protocols were performed during electrical muscle stimulation. Cross-sectional areas (CSA) of smooth muscles were determined from cryo-histological sections stained with Picrosirius Red. Results revealed that maximum smooth muscle tension was 10.4 ± 2.6 N/cm2. Maximum shortening velocity (Vmax) and curvature factor (curv) of the FVR were 0.04 ± 0.01 [optimum muscle length/s] and 0.36 ± 0.15, respectively. The findings of the present study demonstrated significant (P < 0.05) FD [up to 32% maximum muscle force (Fim)] and FE (up to 16% Fim) of gastric muscle tissue, respectively. The FE- and FD-values increased with increasing ramp amplitude. This outstanding muscle behavior is not accounted for in existing models so far and strongly supports the idea of a holistic reflection of distinct stomach structure and function. For the first time this study provides a comprehensive set of stomach smooth muscle parameters including classic biomechanical muscle properties and history-dependent effects, offering the possibility for the development and validation of computational stomach models. Furthermore, this data set facilitates novel insights in gastric motility and contraction behavior based on the re-evaluation of existing contractile mechanisms. That will likely help to understand physiological functions or dysfunctions in terms of gastric accommodation and emptying.